Implementing Joyful Learning Using Arabic Domino Cards to Improve Students' Motivation and Language Understanding - Sasmi, Nur Imana Khofiyani; Baihaqi, Mohammad; Huda, Hisbullah (STIQ Amuntai, 2025)
This research aims to assess the efficacy of the joyful learning method, enhanced through the use of domino cards as a teaching aid, in fostering students’ motivation and understanding in Arabic language instruction. Adopting a quantitative approach, the study employed a quasi-experimental design namely, a one-group pretest-posttest format featuring a cohort of 31 eighth-grade students from MTsN 2 Surabaya. Data were gathered through the administration of pretests and posttests, complemented by classroom observations during the learning process. The statistical findings revealed a marked improvement in student outcomes, with mean scores increasing from 29.42 on the pretest to 74.74 on the posttest. The Paired Sample T-Test yielded a significance value of 0.000 (p < 0.05), indicating that the improvements were statistically significant rather than due to chance. These findings underscore the effectiveness of incorporating game-based elements into instruction, as they help foster a more dynamic, enjoyable, and productive learning environment. As such, the joyful learning approach utilizing domino cards proves to be an innovative and effective pedagogical option for Arabic language education.